Household Collective Models: Three Decades of Theoretical Contributions and Empirical Evidence - Olivier Donni; José Alberto Molina (Institute of Labor Economics (IZA), 2018)
Household collective models celebrate their thirtieth birthday. The collective approach constitutes, perhaps, the microeconomics topic that has produced the largest number of papers (both published and in working paper/mimeo formats) during the last three decades, beginning with the seminal paper published by P.A. Chiappori in Econometrica (Chiappori, 1988). To add to some excellent surveys of household collective models (Strauss et al., 2000; Vermeulen, 2002; Donni and Chiappori, 2011; Chiappori and Mazzocco, 2017), we here perform a bibliographic review of the literature, which includes theoretical contributions, as well as the international empirical evidence related to the collective approach. With respect to the theoretical papers, the collective framework has been used to provide theoretical results for a number of household issues; for example, labour supply, consumption and savings, household production, and intra-household allocation. As for the empirical papers, the international evidence covers the majority of developed and developing countries from all continents.
Keywords: D10; J22; Y10; 330; household; collective models; Pareto efficiency; sharing rule; labor supply; consumption